Effect of Adding Ions - Metal Ions to Pectinase Activity Isolation from Bacillus Subtilis on Bleaching Paper - Mardiana Prasetyani Putri; Anna Roosdiana; Sasangka Prasetyawan; Diah Mardiana (Natural B, Journal of Health and Environmental Sciences, 2013)
Pectinase enzyme used as biocatalyst to overhaul pectat compounds or pectin. Pectinase avtivity was affected by metal ions. The purpose of this study is to determine the effect of adding metal ions on pectinase activity and its inhibition type.. Determination of enzyme activity was based on galacturonic acid produced, which was analyzed by spectrophotometric using DNS reagent. Concentration of metal ions used i.e. Zn2+, Cu2+, Fe3+ were 2-10 mM. The result showed that Vm and KM number without ions were 161.29 µmol/mL minutes and 0.55%(w/v), respectively. While the presence of ions Zn2+, Cu2+, Fe3+ were producing Vmapp 147.06; 156.25 and 153.85µg.ml-1min-1, KMapp of 0.56%; 0.63% and 0.65%, and also KI of 333,33; 41,38; 32,9. The inhibition to metal ions are non-competitif inhibition.